Hydrothermal synthesis and phase formation mechanism of tio2(B) nanorods via alkali metal titanate phase transformation - Yothin Chimupala (2018)
© 2018 Trans Tech Publications, Switzerland. Titanium dioxide (B phase) with 1-D structures was successfully fabricated via a hydrothermal method with a subsequent ion-exchange process and calcination. P25, titanium isopropoxide (TTIP), rutile and also anatase were used as Ti precursors in the alkali hydrothermal system. TTIP promoted an elongation of nanorod morphology whereas the other precursors produced short nanorod structures. The different types of titanium precursors did not have any influence on the phase transformation during the fabrication process. Na2 Ti6 O13 was the primary intermediate product after washing the hydrothermal sample. H2 Ti3 O7 was the secondary intermediate phase obtained following proton-exchange of Na2 Ti6 O13 in HNO3 solution. Finally, the TiO2 (B) phase was the product of calcination of the secondary intermediate product at 400οC for 5 hr. A phase transformation mechanism is presented based on an investigation of products at each of the steps. The effects of the synthesis conditions on tailoring of the crystal morphology are discussed. The growth direction of the TiO2 (B) nanorods was investigated by HR-TEM and SADP. Finally, the metastable phase of TiO2 (B) was shown to be transformed to anatase during thermal treatment at temperatures higher than 400οC.